Role of clarithromycin in the management of multiple infection - Waghray, Pradyut; Bhargava, Samir; Joshi, Devesh K.; Gala, Monil; Muchhala, Snehal S.; Kotak, Bhavesh P. (International Journal of Research in Medical Sciences, 2024)
Clarithromycin, a second-generation semisynthetic macrolide antibiotic, is known for its broad-spectrum antibacterial activity, favorable pharmacokinetic profile, and stability at gastric pH, along with significant anti-inflammatory and immunomodulatory effects. It demonstrates superior efficacy and fewer side effects compared to other macrolides, making it a potent therapeutic option for various bacterial infections. Clarithromycin is approved for use in combination therapy to eradicate Helicobacter pylori and for treating mild to moderately severe respiratory infections such as acute exacerbations of chronic bronchitis (AECB), community-acquired pneumonia (CAP) including infections from Chlamydia, Mycoplasma spp., acute streptococcal pharyngitis, and skin and soft tissue infections. Apart from its usual listed uses, clarithromycin is used in multiple other infections, including upper respiratory tract infections (URTIs) like pharyngitis in penicillin-allergic patients, chronic pharyngitis related to gastroesophageal reflux disease (GERD), sore throat, acute laryngitis, and chronic rhinosinusitis. It is also effective for lower respiratory tract infections (LRTIs) related to chronic obstructive pulmonary disease (COPD), Mycobacterium avium complex (MAC) infections, bronchiectasis, and various other conditions including COVID-19, systemic lupus erythematosus (SLE), bronchiolitis obliterans syndrome post-lung transplant, and H. influenzae infections. During the COVID-19 pandemic, concerns about antimicrobial resistance from the overuse of antibiotics, including azithromycin, highlighted clarithromycin as a preferable alternative due to its superior pharmacodynamics and lower resistance risk. While clarithromycin has a favorable safety profile, it is associated with potential adverse effects such as cardiovascular risks and gastrointestinal disturbances. Its role as a reserve antibiotic highlights its importance in managing resistant infections and in situations where first-line treatments are ineffective or contraindicated.